Multiple neuropeptides produced by sex-specific neurons control activity of the male accessory glands and gonoducts in the silkworm Bombyx mori - Čižmár, Daniel; Roller, Ladislav; Pillerová, Miriam; Sláma, Karel; Žitňan, Dušan (Scientific reports, 2019)
The male accessory glands (AG) and gonoducts of moths develop during metamorphosis and are essential for successful fertilization of females. We found that these reproductive organs are innervated by a sex-specific cluster of peptidergic neurons in the posterior 9th neuromere of the terminal abdominal ganglion (TAG). This cluster of ~20 neurons differentiate during metamorphosis to innervate the accessory glands and sperm ducts. Using immunohistochemistry and in situ hybridization (ISH) we showed that these neurons express four neuropeptide precursors encoding calcitonin-like diuretic hormone (CT-DH), allatotropin (AT) and AT-like peptides (ATLI-III), allatostatin C (AST-C), and myoinhibitory peptides (MIPs). We used contraction bioassay in vitro to determine roles of these neuropeptides in the gonoduct and accessory gland activity. Spontaneous contractions of the seminal vesicle and AG were stimulated in a dose depended manner by CT-DH and AT, whereas AST-C and MIP elicited dose dependent inhibition. Using quantitative RT-PCR we confirmed expression of receptors for these neuropeptides in organs innervated by the male specific cluster of neurons. Our results suggest a role of these neuropeptides in regulation of seminal fluid movements during copulation.
Keywords: Female; Animals; Insect Proteins; neurony; mužské pohlaví; Bombyx; neuropeptidy; Neurons; bourec; zvířata; Neuropeptides; ženské pohlaví; pohlavní dimorfismus; biologická proměna; hmyzí hormony; hmyzí proteiny; Metamorphosis, Biological; Sex Characteristics; Insect Hormones; Male